Dignity, women, and immigration detention - Gerlach, Alice (Abingdon, Oxon ; New York, NY : Routledge, 2023)
This book explores the experience of immigration enforcement for women who have been detained in immigration detention in the UK. Drawing upon in-depth interviews with women who have been in immigration detention centres, Dignity, Women, and Immigration Detention demonstrates how immigration detention violates women's sense of dignity and in doing so, causes women to suffer pains that are incongruent with the administrative purpose of immigration removal centres.The women interviewed were either detained in an Immigration Removal Centre, had spent time in this centre before being released into the UK community, or had been removed to Jamaica following time in immigration detention. This book argues that the current system used by the UK government is unfit for purpose and damaging to many of those who are ensnared within it. In examining dignity violation, lack of autonomy and diminishment, the book also considers possible alternatives to the current practice of incarceration and what can be done to alleviate the harms that are currently inflicted on women during the process of immigration enforcement in the UK. An accessible and compelling read, this book will appeal to students, scholars, and practitioners in criminology, sociology, law, social policy, and all those interested in listening to the unheard voices of detained women.
OCLC-licensed vendor bibliographic record.
Keywords: Women -- Jamaica -- Social conditions; Women -- Great Britain -- Social conditions; Noncitizen detention centers -- Great Britain; Dignity; Great Britain -- Emigration and immigration -- Government policy; SOCIAL SCIENCE / Criminology; SOCIAL SCIENCE / Women's Studies; SOCIAL SCIENCE / Penology